2011
DOI: 10.1007/s00264-010-1178-2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of antiseptics against chondrocytes: What is best for the cartilage in septic joint surgery?

Abstract: In septic joint surgery, the most frequently used antiseptics are polyhexanide, hydrogen peroxide and taurolidine. The aim of this study was to examine the effects of these antiseptics on viability of human chondrocytes. Our hypothesis was that antiseptics and supplemental irrigation with sodium chloride lavage are less toxic on human chondrocytes than treatment with antiseptics only. Primary human chondrocytes were isolated and cultured from six donated human knee joints. Polyhexanide, hydrogen peroxide or ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 14 publications
0
25
0
3
Order By: Relevance
“…The systemic toxicity of taurolidine appears to be low indicated by the finding that healthy volunteers were administered 5 g of taurolidine per day without serious adverse effects [8]. In vitro, toxic effects were observed after 30 min exposure of 0.5% taurolidine to chondrocytes but still being less in comparison to 3% hydrogen peroxide and 0.04% polyhexanide [9].…”
mentioning
confidence: 88%
“…The systemic toxicity of taurolidine appears to be low indicated by the finding that healthy volunteers were administered 5 g of taurolidine per day without serious adverse effects [8]. In vitro, toxic effects were observed after 30 min exposure of 0.5% taurolidine to chondrocytes but still being less in comparison to 3% hydrogen peroxide and 0.04% polyhexanide [9].…”
mentioning
confidence: 88%
“…Chondrocyte isolation was performed as described previously [11]. Cartilage tissue was minced and digested in medium containing 1 mg/ml pronase (Sigma-Aldrich, Deisenhofen, Germany) for 30 minutes at 37°C.…”
Section: Chondrocyte Isolation and Culturementioning
confidence: 99%
“…Literature reviews have revealed very limited data about the effects of polyhexanide exposure to human osteoblasts. In previous studies, we were able to show a superiority of polyhexanide compared with other antiseptics in treating human chondrocytes [11][12][13]. Polyhexanide has a late antiseptic onset of five to 20 minutes and therefore requires prolonged exposure time [14].…”
Section: Introductionmentioning
confidence: 99%